2014
DOI: 10.3390/molecules19021512
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Linear Geranylphenols and Their Effect on Mycelial Growth of Plant Pathogen Botrytis cinerea

Abstract: Natural geranyl compounds are known to exhibit important biological activities. In this work a series of geranylphenols were synthesized to evaluate their effect on the mycelial growth of Botrytis cinerea. Geranyl derivatives were synthesized by direct geranylation reactions between the corresponding phenol derivatives and geraniol, using BF 3 . OEt 2 as catalyst and AgNO 3 as secondary catalyst. Previously reported molecules [geranylhydroquinone (2), geranylhydroquinone diacetate (6) and geranylphloroglucinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 23 publications
4
40
0
Order By: Relevance
“…Furthermore, the semi-synthetic derivatives bakuchiol acetate (5) and bakuchiol methyl eter (6) obtained from bakuchiol were not active against P. cinnamomi; in addition, only compound 5 decreased the mycelial growth of B. cinerea up to 57% at a concentration of 150 mg/L, as reported by Espinoza et al (2014). The antifungal activity is assumed to be associated with the presence of strong electrophilic or nucleophilic systems; other authors have supported this hypothesis, since the presence of free hydroxyl groups in the aromatic ring increases biological activity against mycelial growth of fungus tested in vitro (Bajwa et al 2007).…”
Section: Resultssupporting
confidence: 51%
“…Furthermore, the semi-synthetic derivatives bakuchiol acetate (5) and bakuchiol methyl eter (6) obtained from bakuchiol were not active against P. cinnamomi; in addition, only compound 5 decreased the mycelial growth of B. cinerea up to 57% at a concentration of 150 mg/L, as reported by Espinoza et al (2014). The antifungal activity is assumed to be associated with the presence of strong electrophilic or nucleophilic systems; other authors have supported this hypothesis, since the presence of free hydroxyl groups in the aromatic ring increases biological activity against mycelial growth of fungus tested in vitro (Bajwa et al 2007).…”
Section: Resultssupporting
confidence: 51%
“…This reaction was chosen, between many different synthetic pathways for obtaining prenylated compounds [ 1 , 11 , 12 , 13 , 14 ], because it has been previously used to synthesize a series of synthetic analogs of 3-demethylubiquinone ( 3 ) having one, two, or three methoxy groups in different positions of the quinone moiety [ 6 ]. Alternatively, the reaction was also carried out in acetonitrile instead of dioxane, using AgNO 3 as a secondary catalyst [ 9 ]. The results indicate that both yields and products depend on the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we have found that the inhibitory effect of Captan changed more deeply with concentration, i.e. , 40%, 60% and 80% at 50, 150 and 250 mg/L, respectively [ 9 ]. Both sets of experiments were carried out under the same conditions and, therefore, this remarkable difference is difficult to explain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other synthetic geranylphenols, such as 2-geranyl-5methyl resorcinol and 4-geranyl-5-methyl resorcinol ( Figure 1A), showed antimicrobial and antifungal activities [16][17][18][19] . Recently, our research group has developed the synthesis, structural determination and antifungal activity of a series of linear geranylphenols derivatives of 2-geranylhydroquinones, such 2-geranylphloroglucinol ( Figure 1A) [20][21][22][23][24][25][26] .…”
Section: Linearmentioning
confidence: 99%